Victimisation surveys: What are they good for? - Aromaa Kauko (Temida, 2012)
The author analyzes the usefulness of victimization surveys. The paper is focused of surveys in which nationally representative population samples are surveyed for their personal victimisation experiences, and their attitudes and opinions of issues related to crime and crime control. The author points out the benefits of using victimization surveys, but also explains why most countries have failed to make systematic use of this instrument.